Sex, consent and justice: a new feminist framework - Sikka, Tina (Edinburgh University Press, 2022)
Introduction:The genesis of #metoo --Feminist waves, movements and moments --Consent cultures, alternatives and a new approach --#Metoo past and future --#Metoo and the case for restorative justice --Case studies, methodology and Harvey Weinstein --The case of comedian Louis C.K. --Media personality Jian Ghomeshi --New York University professor Avital Ronell --Actors and comedian Aziz Ansari --Conclusion:#Metoo : new models and new possibilities.